Synchronization and Diversity in Business Cycles: A Network Approach Applied to the European Union - David Matesanz Gomez; Guillermo J. Ortega; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2012)
This paper analyses synchronization in business cycles across the European Union (EU) since 1989. We include both old and new European Union members and countries which are currently negotiating accession, as well as potential European Union members. Our methodological approach is based on the correlation matrix and the networks within, which allows us to summarize the individual interaction and co-movement, while also capturing the existing heterogeneity of connectivity within the European economic system. The results indicate that the synchronization of the old EU countries remained stable until the current financial crisis. Additionally, the synchronization of the new and potential members has approached to the old EU members although we observe the existence of different synchronization levels and dynamics in output growth in single countries as well as in groups of countries. Some countries have achieved an important degree of co-movement (such as the Baltic Republics, Hungary, Slovenia and Iceland), while others have experienced reduced synchronization, or even desynchronization (such as Romania, Bulgaria and even Greece and Ireland).
Keywords: E32; C45; O47; 330; Business cycle synchronization; European Union countries; EU candidates; complex systems; network topology